Tackling the cell wall of the grape berry - Goulão, L.F. (2012)
The cell wall (CW) is the dynamic border of plant cells. In grape berries, the CW decisively accounts for the difference between the pulp and skin cells, with direct consequences on the grape characteristics, wine quality and wine-making methods. The softening of mature berries results from the depolymerisation and solubilisation of CW polymers. Modifications of grape pulp and skin CW provide the flexibility for cell expansion during fruit growth and to modulate the final texture. Wine making and berry processing methods are directly related with the absence, in white wines, or the presence, in red wines, of skin CW in the fermenting must. Anthocyanin extraction depends directly on skin yielding of the pigment upon CW degradation. During fruit growth and ripening, the cooperative action between different enzyme families is capital in CW metabolism. The sequencing and public availability of the Vitis genome allowed us to focus on individual pathways, to profile the expression pattern of isoforms associated with each tissue, developmental phase or stress response, anticipating the effects on berry (and wine) production and quality. Retrieving the sequences of genomic coding regions and the predicted enzymes that act on the Vitis, CW allows us for the first time to tackle the grape berry Cell Wallome